Soignantes et consolatrices ? Femmes contre-révolutionnaires dans la Seconde guerre carliste (Espagne, 1872-1876) - Alexandre Dupont (Genre & Histoire)
This article analyses the transnational mobilization of European women in favor of Carlism during the Carlist war of 1872-1876. The counterrevolutionary ideology legitimates the idea of a natural inequality between men and women, which does not promote, a priori, the political – and even less military – commitment of the latter. In fact, these women, with a few exceptions, are limited to traditional practices of care of the wounded. However, this gendered assignment to non-military tasks paradoxically constitutes an unexpected space of politicization for these women, within quite an involutionist political culture. There is more : these women obtain from their male peers a proper place within the war apparatus, without any reconsideration of gender inequality, which is accepted by both counterrevolutionary men and women.